2022
DOI: 10.1002/hsr2.587
|View full text |Cite
|
Sign up to set email alerts
|

The trend of top five types of poisonings in hospitalized patients based on ICD‐10 in the northeast of Iran during 2012–2018: A cross‐sectional study

Abstract: Background and Aims: Poisoning remains a major health issue in developing countries with high morbidity and mortality rates; also it is one of the most common causes of admission to hospitals. This study aimed to investigate the trend of the top five types of poisonings in hospitalized patients according to the International Statistical Classification of Diseases and Related Health Problems 10th Revision (ICD-10) in Imam Reza hospital, Mashhad, Iran.Methods: This was a cross-sectional study performed from Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Similar to other studies 20 , 26 , 27 , the highest rate of poisoning was observed among individuals aged 20–40 years. In light of the wide range of risk factors associated with poisoning, it is likely that multiple psychosocial, drug availability and economic factors played a role.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to other studies 20 , 26 , 27 , the highest rate of poisoning was observed among individuals aged 20–40 years. In light of the wide range of risk factors associated with poisoning, it is likely that multiple psychosocial, drug availability and economic factors played a role.…”
Section: Discussionsupporting
confidence: 90%
“…Parallel to several previous studies in different countries, medicines were the most prevalent toxin in our study. [ 16 22 23 ] This can be attributed to the common availability of these agents. Opioids were in second place among the poisoning agents in this study.…”
Section: Discussionmentioning
confidence: 99%